Les marges sociales et les franges agricoles se tournent-elles le dos ? - Alice Nikolli; Julie Le Gall; Myriam Laval (Projets de Paysage)
Although there is an increasing demand for local produce this change in food consumption concerns principally people living in city centres with high social and cultural capital. The research presented in this article seeks to answer the following question : Are suburban areas and their inhabitants disconnected from the agricultural fringe areas which supply the city with local food products and, if so, why ? Based on the exploratory notion of the food landscape, we have sought to test the importance of the representations the inhabitants of disadvantaged urban areas have of the agricultural fringes and of the opportunities they provide as food sources. Within the framework of a field study and of a school project conducted in the Minguettes district (in Vénissieux in the agglomeration of Lyon), we have sought to identify the food landscapes of several types of stakeholders and their influence on the modes of food consumption of the inhabitants.